Protective Effect of a GLP-1 Analog on Ischemia-Reperfusion Induced Blood-Retinal Barrier Breakdown and Inflammation - Gonçalves, Andreia (2016)
PURPOSE. Inflammation associated with blood–retinal barrier (BRB) breakdown is a common feature of several retinal diseases. Therefore, the development of novel nonsteroidal antiinflammatory approaches may provide important therapeutic options. Previous studies demonstrated that inhibition of dipeptidyl peptidase-IV, the enzyme responsible for the degradation of glucagon-like peptide-1 (GLP-1), led to insulin-independent prevention of diabetes-induced increases in BRB permeability, suggesting that incretin-based drugs may have beneficial pleiotropic effects in the retina. In the current study, the barrier protective and antiinflammatory properties of exendin-4 (Ex-4), an analog of GLP-1, after ischemia-reperfusion (IR) injury were examined. METHODS. Ischemia-reperfusion injury was induced in rat retinas by increasing the intraocular pressure for 45 minutes followed by 48 hours of reperfusion. Rats were treated with Ex-4 prior to and following IR. Blood–retinal barrier permeability was assessed by Evans blue dye leakage. Retinal inflammatory gene expression and leukocytic infiltration were measured by qRT-PCR and immunofluorescence, respectively. A microglial cell line was used to determine the effects of Ex-4 on lipopolysaccharide (LPS)-induced inflammatory response. RESULTS. Exendin-4 dramatically reduced the BRB permeability induced by IR injury, which was associated with suppression of inflammatory gene expression. Moreover, in vitro studies showed that Ex-4 also reduced the inflammatory response to LPS and inhibited NF-jB activation. CONCLUSIONS. The present work suggests that Ex-4 can prevent IR injury–induced BRB breakdown and inflammation through inhibition of inflammatory cytokine production by activated microglia and may provide a novel option for therapeutic intervention in diseases involving retinal inflammation.